2003
DOI: 10.1111/1467-7687.00259
|View full text |Cite
|
Sign up to set email alerts
|

The development of face and location processing: an fMRI study

Abstract: Although a few developmental fMRI studies have shed some light on the neurological development of either object or spatial processing we still know very little about the development of the 'what' and 'where' processing systems. The present study is the first to address this issue by comparing, concurrently and within the same behavioral paradigm, patterns of functional activation for face processing and location processing in 12 children (10-12 years old) and 16 adults. For both tasks this study found a develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
119
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 99 publications
17
119
0
Order By: Relevance
“…Previous studies have shown a more diffused and distributed pattern of activation in children compared to focused patterns of activation in adults in both linguistic and perceptual (face and object) tasks (Booth et al, 2004;Brown et al, 2005;Casey et al, 2002;Durston et al, 2005;Gaillard et al, 2000;Hertz-Pannier et al, 1997;Passarotti et al, 2003). ERP studies have also shown that neuronal regions are more broadly tuned in young children compared to adults (de Haan et al, 1998;Neville et al, 1992).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown a more diffused and distributed pattern of activation in children compared to focused patterns of activation in adults in both linguistic and perceptual (face and object) tasks (Booth et al, 2004;Brown et al, 2005;Casey et al, 2002;Durston et al, 2005;Gaillard et al, 2000;Hertz-Pannier et al, 1997;Passarotti et al, 2003). ERP studies have also shown that neuronal regions are more broadly tuned in young children compared to adults (de Haan et al, 1998;Neville et al, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…This is analogous to the process of tuning the response properties of single neurons. According to this account, the process of narrowing the response properties facilitates speed of processing for the stimuli or task for which it becomes specialized (Johnson, 2000), and mediates the emergence of greater behavioral expertise and efficiency (Gathers et al, 2004;Gauthier and Nelson, 2001;Passarotti et al, 2003). It has been further suggested that the process of finetuning cortical regions results from changing interactions with other brain regions (Johnson, 2001), and specifically with the recruitment of top-down control mechanisms operating from prefrontal regions to posterior regions (Brown et al, 2005;Casey et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because regression analyses indicated a change in location of parietal activation across adolescence (see Results), an ROI based on the average activation map for the whole group would not accurately represent regions used for the task in both young and old teens (Passarotti et al, 2003). Therefore, we divided teens on age with median (14.93 years) split, and determined significant clusters activated by the task in young and old teens separately using single sample t tests (cluster volume ≥ 943 microliters, p < .05).…”
Section: Data Analysesmentioning
confidence: 99%
“…Further controversy focuses on whether the functional organization of the ventral processing stream is predetermined and established early [5][6][7] or sculpted by experience and learning over time [8,9]. Farah [5] and Gilchrist and McKone [6] propose early established (prior to age 3) face and object recognition systems whereas both Carver [10] and Passarrotti et al [9] suggest changing neural architecture from childhood to adulthood [9,10].…”
Section: Introductionmentioning
confidence: 99%